Hubungan Pengetahuan dan Lama Menderita Hipertensi dengan Manajemen Perawatan Diri pada Pasien di Puskesmas Pakuan Baru, Kota Jambi: Studi Potong Lintang - Alya Aprillini; Indah Mawarti; Lisa Anita Sari; Kamariyah; Yulia Indah Permata Sari (Jurnal Persada Husada Indonesia, 2026)
Research Objective: To examine the associations of knowledge and hypertension duration with self-care management among patients with hypertension at Puskesmas Pakuan Baru, Jambi City. Methodology: This analytical cross-sectional study included 100 patients selected using convenience (accidental) sampling. Respondent characteristics, hypertension knowledge, duration of hypertension, and self-care management were assessed using questionnaires. Frequency distributions were used for descriptive analysis. Pearson chi-square tests were supplemented by Fisher–Freeman–Halton Monte Carlo exact tests because several expected cell counts were below five, and Cramér’s V was reported as the effect-size measure. Results: Most respondents were female (62%), had completed senior high school (48%), were homemakers (42%), had a family history of hypertension (64%), had experienced hypertension for 6–10 years (46%), had fair knowledge (71%), and had fair self-care management (70%). Knowledge was associated with self-care management (Pearson χ²(4) = 40.52, p < 0.001; exact p < 0.001; Cramér’s V = 0.45). Hypertension duration was also associated with self-care management (Pearson χ²(4) = 10.22, p = 0.037; exact p = 0.025; Cramér’s V = 0.23), but the pattern was non-linear: the 6–10-year group had the largest proportion with fair self-care management, whereas the >10-year group had the largest proportion with low self-care management. Conclusion: Knowledge and hypertension duration were associated with self-care management in this sample. The cross-sectional findings do not establish direction or causality, and longer disease duration should not be interpreted as necessarily producing better self-care. Education and follow-up should be tailored to patients’ knowledge and self-care needs across all duration groups.